Factors of Determining Employee Performance: A Study on Organizational Culture and Work Motivation at The Office of Cooperatives, SMEs, Industry, and Trade of Purwakarta Regency - Ismail Ludin; Irman Ramdhan Fauzi; Muhammad Meki Munawar (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Performance is a fundamental aspect in evaluating work planning that has been implemented over a certain period. As a measure of a company's success, performance can provide strategic policy recommendations in the formulation of the next work plan. This study aims to understand the influence of organizational culture and work motivation on the performance of employees at the Department of Cooperatives, SMEs, Trade, and Industry of Purwakarta Regency. The research method used is descriptive verification through multiple linear regression analysis. The research sample consisted of 80 employees from the Department of Cooperatives, SMEs, Trade, and Industry of Purwakarta Regency, using a stratified random sampling method. The results indicate that work motivation and organizational culture positively affect employee performance, with work motivation contributing the most to improved employee performance over a certain period. The overall influence of the variables is 79.2%.